Contribution to the knowledge of the lichens of the Los Azufres Geothermal Field, Michoacán, Mexico - Gomez-Peralta, Marlene (Instituto de Ecología, A.C., 1992)
A list of 100 species of lichens from Los Azufres Geothermal Field s presented. The list comprises 86 new records for the locality, 71 for the state of Michoacan and 24 for Mexico. Data concerning life form and habitat are included for each species; a key for their identification is also included.